Memori Traumatis dalam Novel Jawa Kadang Suriname Sanak Merapi Karya Fuji Riang Prastowo: Kajian Postmemory - Ernawati, Yunita (UPI, 2020)
This study examines the process of transmitting traumatic memory in a novel Kadang Suriname Sanak Merapi by Fuji Riang Prastowo. Through analysis of traumatic transmission it will be known how the formation of a structured transmission. The purpose of this study is to dismantle the structure of transmission through the process of traumatic transmission from the first generation to the next generation. This research uses Postmemory Theory by Marianne Hirsch. The analytical method in this study uses descriptive qualitative analysis. The results of this study are: 1) there are two transmissions that make up the novel, namely the familial transmission of grandmothers and parents so that it leads to affiliative transmission obtained from the office, 2) the Indonesian and Dutch governments experienced hypermasculinization. While Indies and exiles are Infantilized, 3) cropping was done by dominating the story of Indies and exiles as an effort to reconstruct memory.Â AbstrakPenelitian ini mengkaji proses transmisi memori traumatis dalam novel Kadang Suriname Sanak Merapi karya Fuji Riang Prastowo. Melalui analisis transmisi traumatis maka akan diketahui bagaimana pembentukan tramsmisi yang terstruktur. Tujuan penelitian ini adalah membongkar struktur transmisi melalui proses transmisi traumatis dari generasi pertama ke generasi selanjutnya. Penelitian ini menggunakan teori Postmemory yang dipelopori oleh Marianne Hirsch. Metode analisis dalam penelitian ini menggunakan analisis deskriptif kualitatif. Hasil penelitian ini yakni: 1) ada dua transmisi yang membentuk novel, yaitu transmisi familial dari nenek dan orangtua sehingga hal itu mengantarkan kepada transmisi afiliatif yang diperoleh dari kantor; 2) pemerintah Indonesia dan Belanda mengalami Hypermaskulinized. Sedangkan Indies dan orang-orang buangan mengalami Infantilized; 3) cropping dilakukan dengan mendominasikan cerita Indies dan orang buangan sebagai upaya rekonstruksi memori.